2018
DOI: 10.1371/journal.pone.0201627
|View full text |Cite
|
Sign up to set email alerts
|

Risk of retinal artery occlusion in patients with diabetes mellitus: A retrospective large-scale cohort study

Abstract: There is a globally increasing prevalence and incidence of diabetes mellitus (DM). Prolonged hyperglycaemia could lead to both macrovascular damage, such as carotid artery atherosclerosis, and microvascular damage, such as retinal arteriolar narrowing, and might contribute to retinal artery occlusion (RAO). Accordingly, it is important to determine whether DM is a contrubuting factor of RAO. We conducted a retrospective cohort study that included 241,196 DM patients from the Longitudinal Cohort of Diabetes Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…The reported OR were adjusted for sex, age at index date, and other potential confounders present prior to index date. Adjustments were based on knowledge from existing literature, 16,18,19,21,24,25 where potential confounders of the association between each exposure and RAO were identified. The models were adjusted for atrial fibrillation, ischemic heart disease, diabetes, heart failure, arterial hypertension, renal disease, cataract, glaucoma, and retinal vein occlusion.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The reported OR were adjusted for sex, age at index date, and other potential confounders present prior to index date. Adjustments were based on knowledge from existing literature, 16,18,19,21,24,25 where potential confounders of the association between each exposure and RAO were identified. The models were adjusted for atrial fibrillation, ischemic heart disease, diabetes, heart failure, arterial hypertension, renal disease, cataract, glaucoma, and retinal vein occlusion.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This approach for selection of study sample sizes has been used in previous studies. 15 16 To differentiate patients who developed RCE after DM, every patient was tracked from her or his index date of outpatient visit or hospitalisation until December 2013, and their demographic data were recorded (eg, sex and age). Additionally, we collected data of comorbidities, including hypertension (ICD-9-CM codes 401-405), hyperlipidaemia (ICD-9-CM code 272), chronic renal diseases (ICD-9-CM codes 582-588 except 587 and 584) and keratoconjunctivitis sicca (ICD-9-CM codes 710.2 and 370.33).…”
Section: Selection Of Patients and Variablesmentioning
confidence: 99%
“…15 16 Based on the profound effects on the structures involved with ocular diseases of DM including the retinal vessels, ocular surface and optic nerve, 17 it is important to investigate the association between DM and several different ocular diseases with different International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes, aetiologies, manifestations, comorbid conditions, pathophysiology theories and treatment modalities. Our research team planned to find any associations between DM and different ocular diseases such as retinal artery occlusion (ICD-9-CM 362.31 and 362.32), 15 retinal vein occlusion (ICD-9-CM 362.35 and 362.36), corneal ulcer (ICD-9-CM 370.0, excluding 370.07), 16 RCE (ICD-9-CM 371.42) and ischaemic optic neuropathy (ICD-9-CM 377.41, excluding 446.5), and it has attempted to explain the different pathophysiological reasons for these associations.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that patients with RAO were at an increased risk of CVD hospitalization due to comorbid diabetes (risk increased by eight times) and hypertension (risk increased by two times). Diabetes results in macrovascular (like atherosclerosis of major arteries) and microvascular changes (like retinal arteriolar narrowing leading to retinopathy and cerebral small vessel disease) in the vasculature of the whole body [ 14 , 15 ]. Similar vascular changes are caused by hypertension as well.…”
Section: Discussionmentioning
confidence: 99%